Effect of cancer treatment on hypothalamic–pituitary function. Issue 7 (July 2015) - Crowne, Elizabeth; Gleeson, Helena; Benghiat, Helen; Sanghera, Paul; Toogood, Andrew
Summary: The past 30 years have seen a great improvement in survival of children and young adults treated for cancer. Cancer treatment can put patients at risk of health problems that can develop many years later, most commonly affecting the endocrine system. Patients treated with cranial radiotherapy often develop dysfunction of the hypothalamic–pituitary axis. A characteristic pattern of hormone deficiencies develops over several years. Growth hormone is disrupted most often, followed by gonadal, adrenal, and thyroid hormones, leading to abnormal growth and puberty in children, and affecting general wellbeing and fertility in adults. The severity and rate of development of hypopituitarism is determined by the dose of radiotherapy delivered to the hypothalamic–pituitary axis. Individual growth hormone deficiencies can develop after a dose as low as 10 Gy, whereas multiple hormone deficiencies are common after 60 Gy. New techniques in radiotherapy aim to reduce the effect on the hypothalamic–pituitary axis by minimising the dose received. Patients taking cytotoxic drugs do not often develop overt hypopituitarism, although the effect of radiotherapy might be enhanced. The exception is adrenal insufficiency caused by glucocorticosteroids which, although transient, can be life-threatening. New biological drugs to treat cancer can cause autoimmune hypophysitis and hypopituitarism; therefore, oncologists and endocrinologists should be vigilant and work together to optimise patient outcomes.